2004
DOI: 10.1029/2004gl021529
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the onset of equatorial F region irregularities with the sunset terminator observed with the Equatorial Atmosphere Radar

Abstract: The relationship between sunset terminators and the onset of radar backscatter plumes associated with equatorial spread F (ESF) observed with the 47‐MHz Equatorial Atmosphere Radar from October 2002 to April 2004 is discussed. Almost all irregularity echoes began to appear at or before sunset time at the altitude of the apex of the geomagnetic field line connected with the observed area, and the onset time of more than half of the events corresponded exactly to apex sunset time. This tendency should be due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(115 citation statements)
references
References 20 publications
7
106
0
2
Order By: Relevance
“…The ambient ionosphere-thermosphere conditions during the period between the E-region sunset and the most probable onset time, as discussed below, would strongly control the onsets of plasma bubbles. Yokoyama et al (2004) observed VHF coherent echoes from field-aligned irregularities associated with plasma bubbles by using the EAR at Kototabang (20 • magnetic dip angle, see Fig. 1).…”
Section: Equinox Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…The ambient ionosphere-thermosphere conditions during the period between the E-region sunset and the most probable onset time, as discussed below, would strongly control the onsets of plasma bubbles. Yokoyama et al (2004) observed VHF coherent echoes from field-aligned irregularities associated with plasma bubbles by using the EAR at Kototabang (20 • magnetic dip angle, see Fig. 1).…”
Section: Equinox Asymmetrymentioning
confidence: 99%
“…the vertical short-dashed line corresponds to the sunset at the E-region height (120 km), and the long-dashed line corresponds to the sunset at 520 km above the magnetic equator, based upon the fact that most plasma bubble onsets are observed near the sunset at 520 km above the magnetic equator by the Equatorial Atmosphere Radar (EAR) at Kototabang (see Fig. 1) (Yokoyama et al, 2004). The double differentials, and thus the meridional winds (positive northward), oscillated with a period of approximately 7 h during both the equinoxes, and the amplitude was larger in September as compared to that in March.…”
Section: Observationsmentioning
confidence: 99%
“…Multi-beam observations of ESF with the EAR have revealed important aspects in terms of plume spatial distribution that could not be understood with slit-camera-like radar observations (Fukao et al, 2003bOtsuka et al, 2004;Yokoyama et al, 2004Yokoyama et al, , 2005. Yokoyama et al (2004) investigated the accurate onset time of ESF plumes and revealed that it is closely related to sunset at the altitude of the apex of the geomagnetic field line connected to the observed area. Their study indicates that ESF plumes occur exclusively around sunset, and that the coupling between the equatorial and low-latitude regions is very important for the ESF occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Oleh itu, pelbagai peralatan telah dibangunkan bagi mengesan kehadiran strukrur PBB di rantau ini. Antara peralatan yang telah dibangunkan di Kototabang, Indonesia bagi mencerap PBB ialah sistem penderum radio (Saito & Maruyama 2007), radar serakan balik (Ajith et al 2015;Fukao et al 2003;Yokoyama et al 2004Yokoyama et al , 2011 dan pengimejan cahaya teja (Otsuka et al 2004;Shiokawa et al 2006Shiokawa et al , 2004. Walaupun pelbagai kajian telah dilakukan, penjelasan saintifik mengenai punca pembentukan PBB masih belum dapat dikenal pasti dengan tepat.…”
Section: Pengenalanunclassified
“…Pencerapan menggunakan GPS ROTI juga menunjukkan keenam-enam struktur PBB muncul secara berturutan sekitar waktu senja apeks. Hasil kajian ini bertepatan dengan hasil kajian Yokoyama et al (2004) Pencerapan melalui GPS ROTI dapat memantau evolusi PBB secara berterusan dan mengesan perubahan jarak antara PBB dengan lebih terperinci. Hari kemunculan PBB dipercayai dikawal oleh kewujudan struktur seakan gelombang pada bahagian bawah lapisan ionosfera yang seterusnya membentuk PBB melalui proses RTI (Buhari et al 2014).…”
Section: Perbincanganunclassified